(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Enhancing organizational agility is important for successful digital transformation. This study investigates the impact of agile practices on large organizations in Croatia, aiming to determine their effect on HR, process performance, clients, and technology, and to identify correlations among these dimensions. A survey of employees from large Croatian companies revealed that agile methodologies positively impact all organizational dimensions. Key findings indicate improvements in employee motivation, interpersonal relations, internal communication, team productivity, change management, and faster problem detection. Agile practices also enhance client satisfaction, communication, and user participation in product development. However, the adoption of cutting-edge technologies like AI and blockchain remains limited. Strong correlations among the dimensions suggest that improvements in one area positively influence others, underscoring the benefits of agile transformation. This study emphasizes the need for leadership support, cultural readiness, and continuous learning to drive digital change effectively. The findings provide actionable insights for organizations aiming to implement agile methodologies, highlighting their versatility across various sectors including public administration, healthcare, and marketing. By focusing on large companies in Croatia, this research adds a new regional perspective to the global discourse on agile and digital transformation.